Innovations in a Modern Engineering Enterprise in the Context of Industry 4.0 Strategy - Hricova R.; Madzinova R. (Журнал інженерних наук)
Innovations are an essential part of business management in modern society. In addition to large enterprises and research and development centers, small and medium-sized enterprises also hide great innovative potential. Moreover, it is precisely the innovations that lead businesses to permanent growth and prosperity. In addition, from the point of view of Industry 4.0, innovation must be considered as an essential part of the functioning of a modern enterprise, regardless of its size. The article compares statistical indicators that capture enterprises’ innovative activity or inactivity in the Slovak Republic. Enterprises that want to define themselves as innovative should have a suitably prepared and functioning environment, while internal and external conditions are essential. However, it turns out that Slovakian companies have not created suitable conditions for innovation, and in the long term, their interest in innovation is declining. At the same time, because of the industrial revolution, many professions are also changing, and the demands for specific knowledge are not only growing for the newly created ones, but they will also require an active approach to changes, i.e., innovations. Companies must introduce an innovative approach in the education process itself, and as it shows, it will not be possible without a systemic approach.